Infectivity of cysts of the ME-49 Toxoplasma gondii strain in bovine milk and homemade cheese Infecciosidade de cistos de Toxoplasma gondii ME-49 em leite bovino e queijo caseiro - RM Hiramoto; M Mayrbaurl-Borges; AJ Galisteo Jr; LR Meireles; MS Macre; HF Andrade Jr (Universidade de São Paulo, 2001)
OBJECTIVE: Analyze the infectivity and storage resistance of cysts of the ME-49 strain of Toxoplasma gondii in artificially infected bovine milk and homemade fresh cheese. METHODS: Pasteurized bovine milk was infected with 10 cysts/ml of the ME-49 strain of T.gondii and inoculated in different groups of mice, immediately or after storage at 4ºC for 5, 10 and 20 days. Homemade fresh cheese was prepared with artificially infected milk, and also tested in groups of mice, using the same storage process. Infection was identified by the presence of cysts in the brain or serological testing in challenged mice after 5 weeks, confirmed by Western Blot and histology. RESULTS: The infectivity of cysts of the ME-49 strain of T.gondii was maintained in the milk even after storage for 20 days at refrigerator temperatures. Cysts were also able to survive the production process of homemade fresh cheese and storage for a period of 10 days in the same conditions. CONCLUSIONS: These data demonstrated that milk and dairy products could be an important source of T.gondii in human contamination, reinforcing the importance of milk pasteurization before any processing or ingestion. OBJETIVO: Analisar a infecciosidade e a resistência de cistos de T. gondii em leite e queijo fresco caseiro, pela infecção artificial de leite bovino. MÉTODOS: O leite bovino pasteurizado foi infectado artificialmente com 10 cistos/ml de T.gondii cepa ME49 e inoculado em grupos de camundongos, imediatamente ou após ser estocado por 5, 10 e 20 dias a 4ºC. Preparou-se queijo fresco caseiro com leite infectado, sendo testado em grupos de camundongos, utilizando a mesma conservação. A infecção foi detectada pela presença de cistos no cérebro dos camundongos desafiados ou testes sorológicos após cinco semanas, também confirmada por Western Blotting e histologia. RESULTADOS: A infecciosidade dos cistos da cepa ME49 de T.gondii foi mantida mesmo quando armazenado no leite até 20 dias de conservação em condições de refrigeração a 4ºC. Os cistos resistiram ao processo de fabricação do queijo e eram infectantes após um período de 10 dias nas mesmas condições. CONCLUSÕES: Os achados mostraram que o leite e seus derivados podem ser uma importante fonte de contaminação humana pelo T.gondii, reforçando a importância da pasteurização do leite antes de qualquer processamento ou ingestão.